2020
DOI: 10.1029/2020gl090347
|View full text |Cite
|
Sign up to set email alerts
|

Dust Impacts of Rapid Agricultural Expansion on the Great Plains

Abstract: Climate change and land use are altering the landscape of the U.S. Great Plains, producing increases in windblown dust. These increases are investigated by combining coarse mode aerosol observations from the Moderate Resolution Imaging Spectroradiometer (MODIS) sensor in addition to the Aerosol Robotic Network (AERONET) and Interagency Monitoring of Protected Visual Environments (IMPROVE) aerosol monitoring networks. Increasing trends of up to 5%/year in MODIS aerosol optical depth for dust observations are ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 64 publications
(82 reference statements)
0
18
0
Order By: Relevance
“…9 Han and Martin report particles with a 500 nm metal oxide with 700 nm coating of dry AS. Assuming that the metal oxides and the AS are spherical, the immersed surface area per total volume is equal to 0.785 μm 2 in 3.59 μm 3 , or 0.219 μm 2 /μm 3 . In contrast, each droplet in our study contains approximately three immersed particles with mode diameters as high as 310 nm, as can be seen in Figure S1, with AS droplets with diameters of approximately 15 μm.…”
Section: Heterogeneous Efflorescence Of Levitated Ammonium Sulfate Dr...mentioning
confidence: 99%
See 1 more Smart Citation
“…9 Han and Martin report particles with a 500 nm metal oxide with 700 nm coating of dry AS. Assuming that the metal oxides and the AS are spherical, the immersed surface area per total volume is equal to 0.785 μm 2 in 3.59 μm 3 , or 0.219 μm 2 /μm 3 . In contrast, each droplet in our study contains approximately three immersed particles with mode diameters as high as 310 nm, as can be seen in Figure S1, with AS droplets with diameters of approximately 15 μm.…”
Section: Heterogeneous Efflorescence Of Levitated Ammonium Sulfate Dr...mentioning
confidence: 99%
“…It is estimated that approximately one-quarter of mineral dust emissions originate from anthropogenic and agricultural activity, while three-quarters originate from natural sources . However, due to a combination of agricultural expansion and increased likelihood of drought due to climate change, sources of atmospheric dust loading have been shown by aerosol optical depth observations to have increased by approximately 5% per year since 2000 . As such, it is vital to follow and identify the impacts of mineral dust on atmospheric processes.…”
Section: Introductionmentioning
confidence: 99%
“…For example, satellite-derived SO 2 can be an important indicator of power plant emissions (Lu et al, 2013), satellite observations of CO show the impact of global pollution transport (NASA, 2015), and satellite observations of "aerosol optical depth" have been used quantify global exposure to fine PM (van Donkelaar et al, 2010). Beyond tracking fuel combustion, satellite data have been used to assess upstream emissions from energy processes, such as dust impacts of cropland expansion from bioenergy (Lambert et al, 2020) and air emissions associated with the pre-harvest sugarcane field burning phase of ethanol production in Brazil (Tsao et al, 2012).…”
Section: Health and Air Quality Impactsmentioning
confidence: 99%
“…Such soils are especially vulnerable to deflation (erosion by wind of loose sediment) when subjected to extended drought-caused losses in vegetation and/ or certain types of ground disturbance and/or heavy tilling. Lambert et al (2020) reported that given the expansion of agriculture in many parts of the U.S. Great Plains, increases in drought and associated crop losses are already causing increases in erosion and dust emission. Farmers in Curry County and other parts of eastern New Mexico, observing drought-stricken fields, are concerned that future increased windiness could result in significant erosion and dust emission, essentially establishing a "new Dust Bowl'' (Albuquerque Journal, Jan. 2, 2021).…”
Section: Impacts On Eolian Landscapes and Eolianmentioning
confidence: 99%